If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -6p = 5 + -9p Add '-5' to each side of the equation. 5 + -5 + -6p = 5 + -5 + -9p Combine like terms: 5 + -5 = 0 0 + -6p = 5 + -5 + -9p -6p = 5 + -5 + -9p Combine like terms: 5 + -5 = 0 -6p = 0 + -9p -6p = -9p Solving -6p = -9p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '9p' to each side of the equation. -6p + 9p = -9p + 9p Combine like terms: -6p + 9p = 3p 3p = -9p + 9p Combine like terms: -9p + 9p = 0 3p = 0 Divide each side by '3'. p = 0 Simplifying p = 0
| 250/20= | | 0.4(2x+4)=4.8 | | -5(-10-a)=60 | | 8x+9y=18 | | 44=4x-12 | | 8y+9y=18 | | y=-1.7x+2.2 | | 750-50h=-185+35h | | 4q+5-q=2(q-3) | | 5x+14=3x-13 | | 4(-f+(-5))=0 | | -15+35= | | 7x+18=x | | 57x+18=x | | 3y-1=y+19 | | -2(e-4)=-4 | | x=-4y+12 | | 1.5(2x+5)=16.5 | | -6.2(4x+6)-2.9(3x-5)= | | 5d-10=14-3d | | 81y^4-1=0 | | xy^2-5xy+6x=0 | | 7(3+n)=140+21 | | -4y+8=(2y-2)-2(-16+8y) | | 4(2c+5)=28 | | 14p+4=4p | | x^2-5xy+6x=0 | | 2a-14-10a=10-24a-5 | | 28=2(7+n) | | 0.5x+y=3 | | 0.5(2x+4)=4.8 | | 10=5(b-3) |